To solve the expression (-2)×(1-5)÷(2-3)×(5-6)÷(3-4), we can use the order of operations:
First, we start by evaluating the expression inside the parentheses.
(-2)×(1-5) becomes (-2)×(-4). We can multiply these two numbers:
(-2)×(-4) = 8.
Next, we evaluate (2-3):
(2-3) = -1.
And finally, we evaluate (5-6):
(5-6) = -1.
Now we substitute these values back into the original expression:
8÷(-1)×(-1)÷(3-4).
Next, we evaluate 3-4:
(3-4) = -1.
Now we can substitute this value into the expression:
8÷(-1)×(-1)÷(-1).
Next, we use the properties of operations to simplify the expression.
8÷(-1) = -8. And (-1)×(-1) = 1.
So the expression simplifies to:
-8×1÷(-1).
Finally, we multiply -8 by 1:
-8×1 = -8.
And then we divide -8 by -1:
-8÷(-1) = 8.
Therefore, the solution to the expression (-2)×(1-5)÷(2-3)×(5-6)÷(3-4) is 8.
Use the properties of operations and the rules for multiplying and dividing to solve. (-2)×(1-5)÷(2-3)×(5-6)÷(3-4)
1 answer